Mycobacterium smegmatis Vaccine Vector Elicits CD4+ Th17 and CD8+ Tc17 T Cells With Therapeutic Potential to Infections With Mycobacterium avium - Kannan, Nisha; Haug, Markus; Steigedal, Magnus; Flo, Trude Helen (Frontiers in Immunology, 2020)
Mycobacterium avium (Mav) complex is increasingly reported to cause non-tuberculous infections in individuals with a compromised immune system. Treatment is complicated and no vaccines are available. Previous studies have shown some potential of using genetically modified Mycobacterium smegmatis (Msm) as a vaccine vector to tuberculosis since it is non-pathogenic and thus would be tolerated by immunocompromised individuals. In this study, we used a mutant strain of Msm disrupted in EspG3, a component of the ESX-3 secretion system. Infection of macrophages and dendritic cells with Msm ΔespG3 showed increased antigen presentation compared to cells infected with wild-type Msm. Vaccination of mice with Msm ΔespG3, expressing the Mav antigen MPT64, provided equal protection against Mav infection as the tuberculosis vaccine, Mycobacterium bovis BCG. However, upon challenge with Mav, we observed a high frequency of IL-17-producing CD4+ (Th17 cells) and CD8+ (Tc17 cells) T cells in mice vaccinated with Msm ΔespG3::mpt64 that was not seen in BCG-vaccinated mice. Adoptive transfer of cells from Msm ΔespG3-vaccinated mice showed that cells from the T cell compartment contributed to protection from Mav infection. Further experiments revealed Tc17-enriched T cells did not provide prophylactic protection against subsequent Mav infection, but a therapeutic effect was observed when Tc17-enriched cells were transferred to mice already infected with Mav. These initial findings are important, as they suggest a previously unknown role of Tc17 cells in mycobacterial infections. Taken together, Msm ΔespG3 shows promise as a vaccine vector against Mav and possibly other (myco)bacterial infections.